Attenuation of hemodynamic pressor response to laryngoscopy and endotracheal intubation by intravenous fentanyl in elective surgery under general anesthesia: A randomized controlled trial using three different doses - Hazra, Rajdip; Syiem, Yarilang Rozanna; Maitra, Sanjay; Chakraborty, Sisir; Sarkar, Manabendra (Asian Journal of Medical Sciences, 2023)
Background: Direct laryngoscopy and endotracheal intubation elicit hemodynamic pressor responses which may be hazardous in high risk patients. Fentanyl, a low cost synthetic opioid, when used judiciously, may be a good option to attenuate this stress response. Aims and Objectives: The present study has been conducted to compare the efficacy of three different doses of intravenous fentanyl in attenuation of hemodynamic pressor response to laryngoscopy and endotracheal intubation in elective surgery under general anesthesia. Materials and Methods: It was a double-blinded randomized controlled trial. A total of 90 patients of American Society of Anesthesiologists physical status I and II, 55 male and 35 female, aged between 20 and 55 years, were randomized into three groups receiving 2, 3, and 4 μg/kg of injection fentanyl, respectively, administered intravenously 5 min before direct laryngoscopy and endotracheal intubation. Results: There were significant differences in hemodynamic variables among all three groups at 1, 3, 5, and 10 min after endotracheal intubation. Just after endotracheal intubation; heart rate, mean arterial pressure, and diastolic arterial pressure – all these variables showed significance between 3 μg/kg and 4 μg/kg groups only. Incidence of nausea/vomiting showed statistical significance between 2 μg/kg and 4 μg/kg groups only. Conclusion: In our double-blinded randomized controlled trial, 4 μg/kg of injection fentanyl administered 5 min before laryngoscopy and intubation, has showed superior efficacy in suppressing hemodynamic stress responses associated with it. Further, larger trials are needed to confirm our findings.